Point‐based spatial colour sampling in Milano‐Retinex: a survey. Issue 6 (1st June 2018) - Lecca, Michela; Simone, Gabriele; Bonanomi, Cristian; Rizzi, Alessandro
Abstract : Milano‐Retinex is a family of Retinex‐inspired spatial colour algorithms mainly developed for colour image enhancement. According to the Retinex theory, a Milano‐Retinex algorithm takes as input an RGB image and processes the colour intensities of each pixel (i.e. the target) based on the spatial distribution of the colour intensities sampled in a surrounding region. The output is an RGB image, with locally adjusted colours and contrast. In Milano‐Retinex family, different ways of spatial sampling are implemented. This study reviews and compares these sampling characteristics within a group of Milano‐Retinex algorithms developed in the last decade, from Random Spray Retinex (2007) to the gradient‐based colour sampling schemes GREAT and GRASS (2017). Instead of exploring the target neighbourhood by random paths as the original Retinex algorithm does, these methods consider sets of pixels, randomly or deterministically defined, including all the image pixels or a part of them, such as random sprays or image edges. They replace the ratio‐reset‐threshold‐product‐average mechanism of the original Retinex with equations re‐working maximal intensities over the sampled sets. The performance of these approaches is compared with more than 200 images of indoor and outdoor scenes, captured by commercial cameras under several different conditions.